2021
DOI: 10.1186/s13063-021-05786-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of acupotomy for knee osteoarthritis: study protocol for a randomized controlled trial

Abstract: Background Knee osteoarthritis (KOA) is one of the most common musculoskeletal disorders. Acupotomy may be effective for KOA, but the evidence is limited. This trial aims to determine the effectiveness and safety of acupotomy for KOA. Methods/design This is a parallel-group, assessor-blinded randomized controlled trial. Two hundred patients with KOA will be recruited and randomly assigned to two groups (group A or group D) in a 1:1 ratio. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This finding indicated that the immediate analgesic effect of the drug was better and the long-term effect was worse, which is consistent with the above follow-up ranking results. In terms of WOMAC function, the comparison between the <4-week and ≥4-week subgroups showed OT lost its ranking advantage over AT and LT, which may be related to the slow onset of AT and LT ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated that the immediate analgesic effect of the drug was better and the long-term effect was worse, which is consistent with the above follow-up ranking results. In terms of WOMAC function, the comparison between the <4-week and ≥4-week subgroups showed OT lost its ranking advantage over AT and LT, which may be related to the slow onset of AT and LT ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acupotomy therapy is a minimally invasive therapy of traditional Chinese medicine, which combined both traditional acupuncture and modern surgical principles, and could dredge meridians and release tissue adhesion because of the specific bit tool of acupotomy could needle, cut, strip, and shove. 25 Acupotomy has been shown to be beneficial in the treatment of KOA in clinical trials, and it is simple, inexpensive, effective, and safe. 26 Biomechanical factors are currently recognized as the pathogenesis of KOA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that it starts from the degenerative changes of knee articular cartilage, gradually affects the subchondral plate and joint capsule, and finally leads to the progressive destruction of articular cartilage and synovial inflammation [ 12 ]. Patients with KOA always have clinical symptoms such as joint pain, swelling, and mobility impairment [ 13 15 ]. KOA is classified as joint pain in traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%